2007
DOI: 10.1007/s10147-007-0681-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of paclitaxel with carboplatin or gemcitabine, and effects of CYP3A5 and MDR1 polymorphisms in patients with urogenital cancers

Abstract: The hematological side effects of paclitaxel were intensified by gemcitabine, and were correlated with paclitaxel pharmacokinetics. Monitoring of the serum concentration of paclitaxel will facilitate the therapy, with less myelosuppression and without any loss of therapeutic efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Several studies have reported that gemcitabine activates nF-κB (13,14,16,20) and Mdr (27). our results also showed that gemcitabine enhanced nF-κB protein expression in both our pancreatic cancer cell lines.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies have reported that gemcitabine activates nF-κB (13,14,16,20) and Mdr (27). our results also showed that gemcitabine enhanced nF-κB protein expression in both our pancreatic cancer cell lines.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies have reported associations between the ABCB1 genotype and different kinetic parameters, such as the AUC [108] and the apparent total clearance after : increased, ; decreased, AEs adverse effects, AUC area under the concentration-time curve, AUC/D dose-dependent AUC, AUC x AUC from time 0 to time x, AUC x /D dose-dependent AUC x , C concentration, C x concentration at time x, C x /D dose-dependent C x , CL apparent total clearance after intravenous administration, CL/F apparent total clearance after oral administration, C max maximum concentration, C max /D dosedependent C max , D required dose, ER extraction rate, F bioavailability, NS not significant, t elimination half-life, t max time to attain C max a X denotes that this variant was tested [109,110] of paclitaxel, whereas other studies did not find any significant associations [111,112]. Two studies reported an association with survival in 43 Chinese gastric cancer patients [113] and in 109 Korean patients with metastatic breast cancer [114].…”
Section: Taxanesmentioning
confidence: 88%
“…The DOC AUC and CL have been reported, in most cases, to be unaffected by ABCB1 SNPs [63,64] but one study in 92 Caucasians patients reported a significantly decreased DOC CL only in ABCB1 1236TT homozygous (-25%) and no influence of 2677G>T/A and 3435C>T polymorphisms [65]. A weak association between PK parameters and ABCB1 genetic status has been also described for PAC [66][67][68]. For example, in the study of Nakajima et al, patients possessing the 3435T allele had a significantly higher AUC of 3'-phydroxyPAC (the main PAC metabolite) compared to those possessing the 3435C allele.…”
Section: Abcb1mentioning
confidence: 84%